POTENSI EKSTRAK DAUN MANGROVE (Sonneratia alba) SEBAGAI ANTIBAKTERI TERHADAP Salmonella, Staphylococcus aureus, DAN Escherichia coli - Manuhuttu, D; Saimima, Nur A (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2021)
Background: Indonesia's food industry is growing well, both in the types and variations of food products as well as in thevolume and quality of its production, however this growth have to deal with the challenge of chemical abuse thatendangers public health. Therefore it is need to attempt alternative ways which engage natural ingredients for theprocess of preservation, one of them is the utilization of mangrove leaf. This study aims to understand the activity ofmangrove leaf extract Sonneratia alba as an antibacterial agent, in which the type of solvent used is ethyl acetate solvent(polar), methanol (semi-polar) and hexane (non-polar).Method: Research methodology has extract samples from this leaves tread mangrove the process leaves preparasisample tread a horse, and the process of extracting and percent rendemen.Extraction done in maceration with weigh asmuch as 50 grams tread dry leaves mangrove 150 ukuran ml methanol solvent, heksan and ethyl acetate.Result: The research results obtained extracts mangrove leaves as an antibacterial activity sonneratia alba having goodbacteria gram positive or negative grams and the secondary these compound which is found in extract terpenoidsonneratia alba is , and tannin saponin.Conclusion: The extract best obtained from the use of these three solvent is of an extract with a solvent ethyl acetate (spring polar ) having effectiveness as an antibacterial.